Analysis of SNR at the humidity atmosphere using millimeter-wave - Elmutasim, Imadeldin Elsayed; Izzeldin Ibrahim, Mohamed Abdelaziz (Institute of Electrical and Electronics Engineers Inc., 2021)
Air quality is becoming a more serious subject in recent times, particularly when influencing human beings, the environment, and service sectors such as meteorology, healthcare, and wireless communication technology. The public is concerned about atmospheric contents, which could negatively impact while conveying infections, particles, and unwanted gas. The wide affected range of service sectors could become hot weather, which is well known at Qatar state and whole gulf countries. Moreover, the contamination from various manufacturers in desert weather gives a unique opportunity to study the impact of climate behavior and provide attention to the values obtained during the seasons. This work has investigated Qatar's humidity, one of the environmental effects that combine dry air with water vapor and lead to reduced air quality hence the human respiratory health using millimeter-wave frequencies as a promising upcoming technology band. The study utilized a gas path loss model that respects humidity with other parameters to achieve an efficient value reliable wireless communication system to help the cutting-edge innovation suppliers in the comparable areas reinforce the service via accomplishing customer demands. The model uses the highest and lowest humidity values, 29g/m3 and 13g/m3, respectively, in high frequencies and under the two fixed bandwidths 28 and 112 Mbps. The result demonstrated the stark contrast in attenuation values, particularly when reaching the peak humidity that gives notification that the capacity could become swinging even under the fixed bandwidth based on SNR affected by humidity, which shows more influence than other parameters such as temperature and pressure. The work utilizes comprehensively real values to incorporate the influences in link attenuation and capacity throughput to obtain a robust model that would become significant to wireless designers.